Metal–Organic Gels from Silver Nanoclusters with Aggregation‐Induced Emission and Fluorescence‐to‐Phosphorescence Switching. (22nd October 2019) - Xie, Zengchun; Sun, Panpan; Wang, Zhi; Li, Hongguang; Yu, Longyue; Sun, Di; Chen, Mengjun; Bi, Yuting; Xin, Xia; Hao, Jingcheng
Abstract: Luminescent metal nanoclusters (NCs) are emerging as a new class of functional materials that have rich physicochemical properties and wide potential applications. In recent years, it has been found that some metal NCs undergo aggregation‐induced emission (AIE) and an interesting fluorescence‐to‐phosphorescence (F‐P) switching in solutions. However, insights of both the AIE and the F‐P switching remain largely unknown. Now, gelation of water soluble, atomically precise Ag9 NCs is achieved by the addition of antisolvent. Self‐assembly of Ag9 NCs into entangled fibers was confirmed, during which AIE was observed together with an F‐P switching occurring within a narrow time scale. Structural evaluation indicates the fibers are highly ordered. The self‐assembly of Ag9 NCs and their photoluminescent property are thermally reversible, making the metal–organic gels good candidates for luminescent ratiometric thermometers. Abstract : Eine lösungsmittelinduzierte Gelierung von Ag‐Nanoclustern wurde mit atomarer Genauigkeit erreicht. Das Metall‐organische Gel zeigt eine aggregationsinduzierte Emission mit Fluoreszenz‐Phosphoreszenz‐Schaltung sowie reversible Veränderungen unter Heiz‐Kühl‐Zyklen.